Polychaeta Communities in Subtidal Zone Soft Substrate of Manado Bay, North Sulawesi - Lumingas, Aaron R. T.; Boneka, Farnis B.; Ompi, Medy; Mamangkey, Noldy G. F.; Manembu, Indri S.; Undap, Suzanne L.; Lumingas, Lawrence J. L. (Sam Ratulangi University, 2022)
This study aims to analyze the structure of the Polychaeta community on the soft substrate of the subtidal zone in Manado Bay. Samples were taken by grab at 3 stations namely ST1 located at a depth of 8 m with black mud substrate; ST2 is located at a depth of 26 m with blackish sand substrate, and ST3 are located at a depth of 18 m with blackish sand as a substrate. From the three sampling stations, 27 species of 253 Polychaeta individuals were identified. Station 1, which is located near the mouth of the Bailang River, has high individual abundance but low species diversity. Station 2, which is located near the Megamas area, has moderate individual abundance but high species richness. Station 3, which is located around the Faculty of Medicine, Unsrat Malalayang, has low individual abundance but high species richness. Substrate types and anthropogenic disturbances such as enrichment of organic matter are thought to be determinants of individual abundance, composition, and species richness of Polychaeta in Manado Bay.Keywords: Polychaeta; biodiversity; soft substrate; Manado BayAbstrakÂ Penelitian ini bertujuan untuk menganalisis struktur komunitas Polychaeta pada substrat lunak zona subtidal di Teluk Manado. Sampel diambil dengan grab pada 3 stasiun yakni ST1 terletak pada kedalaman 8 m dengan substrat lumpur berwarna hitam; ST2 terletak pada kedalaman 26 m dengan substrat pasir berwarna kehitaman; dan ST3 terletak pada kedalaman 18 m dengan substrat pasir berwarna kehitaman. Dari tiga stasiun sampling tersebut berhasil diidentifikasi 27 spesies dari 253 individu Polychaeta. Stasiun 1 yang terletak dekat muara Sungai Bailang memiliki kelimpahan individu tinggi tetapi keanekaragaman spesies rendah. Stasiun 2 yang terletak dekat kawasan Megamas memiliki kelimpahan individu sedang tetapi kekayaan spesies tinggi. Stasiun 3 yang terletak di sekitar pemukiman belakang Fakultas Kedokteran Unsrat Malalayang memiliki kelimpahan individu rendah tetapi kekayaan spesies tinggi. Jenis substrat dan gangguan antropogenik seperti pengayaan bahan organik diduga merupakan faktor penentu kelimpahan individu, komposisi dan kekayaan spesies Polychaeta di Teluk Manado.Â Kata Kunci: Polychaeta; keanekaragaman hayati; substrat lunak; Teluk Manado